Super Bulk and Interfacial Toughness of Amylopectin Reinforced PAAm/PVA Double‐Network Hydrogels via Multiple Hydrogen Bonds - Yikun Zhang; Dapeng Li; Yiwan Huang; Shijun Long; Haiyan Li; Xuefeng Li (Macromolecular Materials and Engineering)
Abstract A simple, multiple‐hydrogen‐bond approach to fabricating physically crosslinked, Amylopectin reinforced polyacrylamide/poly(vinyl alcohol) (Amy/PAAm/PVA) double‐network (DN) hydrogels with super toughness in bulk and at solid interfaces is reported. The Amy/PAAm/PVA DN hydrogels exhibit high tensile strength (854.1 kPa), high extensibility (≈eight times), high bulk toughness (4094.8 kJ m−3), good self‐recovery property (≈92% of self‐recovery at room temperature), and strong adhesion to nonporous glass surfaces (≈158 kPa). Such tough and adhesive DN hydrogels have great potential for various applications in engineering artificial soft tissues, flexible electronics, and wearable devices.